Liquidity (risk) concepts: definitions and interactions - Kleopatra Nikolaou (European Central Bank (ECB), 2009)
We discuss the notion of liquidity and liquidity risk within the financial system. We distinguish between three different liquidity types, central bank liquidity, funding and market liquidity and their relevant risks. In order to understand the workings of financial system liquidity, as well as the role of the central bank, we bring together relevant literature from different areas and review liquidity linkages among these three types in normal and turbulent times. We stress that the root of liquidity risk lies in information asymmetries and the existence of incomplete markets. The role of central bank liquidity can be important in managing a liquidity crisis, yet it is not a panacea. It can act as an immediate but temporary buffer to liquidity shocks, thereby allowing time for supervision and regulation to confront the causes of liquidity risk.
Keywords: G10; G20; 330; Central Bank; liquidity; LLR; risk; Finanzmarkt; Geldmarkt; Bankenliquidität; Marktliquidität; Liquidität; Zentralbank; Unvollkommener Markt; Asymmetrische Information